2020
DOI: 10.1051/parasite/2020018
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of Toxoplasma gondii infection in primary school children in Henan province, central China

Abstract: Toxoplasma gondii is an obligate intracellular protozoan parasite with global distribution. However, data on T. gondii infection among children in primary school in Henan province, central China were lacking. In this study, 2451 serum samples of primary school children in this province were collected from September 2015 to October 2018 and evaluated for T. gondii antibodies using an enzyme-linked immunosorbent assay (ELISA). The overall seroprevalence was 9.51% (233/2451), of which 7.59% (186/2451) showed IgG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…There is still no clear pathological evidence to understanding the vertical transmission of T. gondii infection and the possible mechanism for LBW in newborn babies. Eating raw or insufficiently cooked meat, improper hygiene practices, such as handwashing after handling raw meat, vegetables or fruits, and contact with domestic pets are the major paths of T. gondii transmission [ 37 , 38 ]. Conversely, the risk of LBW is multifactorial, including maternal host and behavioral factors, several sociodemographic factors, and certain environmental exposures [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is still no clear pathological evidence to understanding the vertical transmission of T. gondii infection and the possible mechanism for LBW in newborn babies. Eating raw or insufficiently cooked meat, improper hygiene practices, such as handwashing after handling raw meat, vegetables or fruits, and contact with domestic pets are the major paths of T. gondii transmission [ 37 , 38 ]. Conversely, the risk of LBW is multifactorial, including maternal host and behavioral factors, several sociodemographic factors, and certain environmental exposures [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected from 2451 primary school children in four cities of Henan province, as previously described [31]. The same sera were used in both studies.…”
Section: Study Site and Sample Collectionmentioning
confidence: 99%
“…This might be due to the different methods used in our study (MAT vs ELISA). A study conducted in Henan province (China) using ELISA indicated that the overall seroprevalence of T. gondii in primary school children was 9.51% [14]. Furthermore, students in SYAU are enrolled from all provinces around China, whereas students participating in our study are mainly from Anhui province.…”
Section: Discussionmentioning
confidence: 98%